2016
DOI: 10.1038/ncomms11662
|View full text |Cite
|
Sign up to set email alerts
|

Potent social synchronization can override photic entrainment of circadian rhythms

Abstract: Circadian rhythms in behaviour and physiology are important for animal health and survival. Studies with individually isolated animals in the laboratory have consistently emphasized the dominant role of light for the entrainment of circadian rhythms to relevant environmental cycles. Although in nature interactions with conspecifics are functionally significant, social signals are typically not considered important time-givers for the animal circadian clock. Our results challenge this view. By studying honeybee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 57 publications
9
86
0
Order By: Relevance
“…This internal rhythm is generated by a circadian clock (~24 hours long), that regulates numerous physiological and behavioral processes including the sleep/wake cycle. The circadian clock can be synchronized to the environment by different cues (or Zeitgebers ) [5,20], such as light [21], temperature [22], food availability [23], and social interactions [24,25]. Internal clocks are advantageous to animals, enabling them to predict daily recurring events – even in the absence of environmental cues – and aligning their internal processes to the environment [20,26], as for feeding and metabolism [27].…”
Section: Circadian Regulation Of Sleep/wake Statesmentioning
confidence: 99%
“…This internal rhythm is generated by a circadian clock (~24 hours long), that regulates numerous physiological and behavioral processes including the sleep/wake cycle. The circadian clock can be synchronized to the environment by different cues (or Zeitgebers ) [5,20], such as light [21], temperature [22], food availability [23], and social interactions [24,25]. Internal clocks are advantageous to animals, enabling them to predict daily recurring events – even in the absence of environmental cues – and aligning their internal processes to the environment [20,26], as for feeding and metabolism [27].…”
Section: Circadian Regulation Of Sleep/wake Statesmentioning
confidence: 99%
“…For chronobiologists, the scope for a Wild Clock approach has been highlighted by evidence that clock regulation in real-world contexts tends to be more complex, and may differ, from expectations based on laboratory studies [109,121,205]. Hence, an important import from ecology is an appreciation of the complexity of the environmental signals that affect biological clocks.…”
Section: (C) Prospects Of a Wild Clock Approachmentioning
confidence: 99%
“…of zeitgebers that entrain animal clocks in a more complex and natural context, but also show that non-photic time givers may override photic entrainment [107][108][109].…”
Section: Converging Key Concepts Of Both Fields: Plasticity and Chronmentioning
confidence: 99%
“…Moreover, the disruption and modification of forager honey bee circadian rhythms may affect the overall bee colony temporal structure through disruption of social entrainment. Previous studies have reported that the rhythms of honey bee foragers serve to synchronize the rhythms of the hive-bound nurse bees 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Average activity duration was calculated by subtracting the onsets from the offsets of each day (offset time -onset time) and then averaging (Supplemental Figure 4A Sleep was analyzed from the activity data collected from the LAMs. Several studies have shown that lack of movement (beam interruptions) for five consecutive minutes serves as a reliable measure for sleep in honey bees 29,44,45 . Consistent with these studies we defined sleep as 5 min or longer bouts of inactivity.…”
Section: Behavioral Metrics (Data Analysis)mentioning
confidence: 99%